State of mental health, sleep status, and the interaction with health-related quality of life in HIV-infected Chinese patients during the COVID-19 pandemic - Du, Juan; Li, Jin; Liang, Han; Wang, Fuxiang; Lin, Yuanlong; Shao, Bing (BMC public health, 2024)
To describe how mental health and sleep status influence the health-related quality of life (HRQOL) of people living with HIV/AIDS (PLWHA) during the novel coronavirus disease 2019 (COVID-19) pandemic, and to apply targeted interventions to improve the HRQOL. A web-based online questionnaire survey was administered. Descriptive analysis was used to depict the mental health and sleep status. Correlation analysis and the structural equation model (SEM) method were used to analyze the influence of mental health and sleep status on HRQOL in PLWHA. After excluding 24 unqualified questionnaires, a total of 490 participants in this survey were included in the statistical analysis. Of the participants, 66.1% and 55.1% reported mild or worse symptoms of depression and anxiety, respectively. Overall, 70.0% had varying degrees of sleep problems. Correlation analysis showed that anxiety had the strongest correlation with sleep disturbances and sleep quality (R = 0.588 and 0.551, respectively), while depression had the strongest correlation with the HRQOL psychological and physical domains (R = - 0.759 and - 0.682, respectively). SEM analysis showed that depression, sleep quality, and psychological domains had the greatest item load on mental health, sleep status, and HRQOL (093, 0.82, and 0.89, respectively). Mental health had a more significant influence than sleep status on HRQOL, as indicated by factor loading (- 0.75 and - 0.15, respectively). There were more severe mental health and sleep problems among PLWHA during the COVID-19 pandemic, thus, mental health intervention, especially to relieve depression symptoms, may be the most important approach to improve the HRQOL among PLWHA.